"Africans, we know how to adapt indeed": Adaptations to family planning and reproductive health services in humanitarian settings in Nigeria during the COVID-19 pandemic. - Emily Evens; Ashley Ambrose; Bamidele Bello; Kate Murray; Nadia Tefouet; Adesegun Fatusi; Bridget Nwagbara; Mercy Riungu; Tijani Maji; Hadiza Khamofu; Jean Christophe Fotso; Ndola Prata (Public Library of Science (PLoS), 2023)
On March 30, 2020, the Government of Nigeria implemented its first COVID-19 related lockdown. We worked with two humanitarian projects in Nigeria, the Integrated Humanitarian Assistance to Northeast Nigeria (IHANN II) in Borno State and the United Nations High Commissioner for Refugees South-South Health and Nutrition Intervention (UNHCR-SS-HNIR) for Cameroon Refugees and vulnerable populations in Cross River State, to document the programmatic adaptations to Family Planning/Reproductive Health (FP/RH) services in response to COVID-19 and identify successes and challenges of those adaptations. A mixed methods approach including quantitative analysis of data from routine programmatic activities, qualitative data from in-depth interviews (IDIs) with project staff and process documentation of programmatic activities and modifications was used to 1) identify modifications in FP/RH services due to COVID-19, 2) understand staff perception of their utility and impact, and 3) gauge trends in key FP/RH in-service delivery indicators to assess changes prior to and after the March 2020 lockdown. Monitoring data shows notable declines in service utilization after lockdowns in antenatal care, postnatal care, and outreach campaigns, followed by a return to pre-lockdown levels by July 2020. Results show projects introduced numerous COVID-19 precaution strategies including: community sensitization; triage stations and modification of service flow in facilities; and appointment scheduling for essential services. Findings from IDIs speak to a well-coordinated and implemented COVID-19 response with project staff noting improvements in their time management and interpersonal communication skills. Lessons learned included the need to better sensitize and educate communities, maintain FP commodities and increase support provided to health workers. Deliberate adaptations in IHANN II and UNHCR-SS-HNIR projects turned challenges to opportunities, ensuring continuity of services to the most vulnerable populations.